Applications of mobile information processor edge-over-edge molecular wires with high-performance thermoelectric generators - Binoj, J. S. (Hindawi Limited, 2022)
If high-efficiency organic isotherm models for mobile processors can be found, a variety of energy harvesting devices, such as Peltier coolers composed of flexible and transparent thin-film materials, might be manufactured. The thermoelectric characteristics of three zinc porphyrins (ZnP) were studied. Theoretical analyses of electron transport across a potassium (Zn-Diphenyl porphyrin: Zn-DPP) molecular sandwiched between electrode surface with three distinct connections were investigated. The contribution of this research is to see what happens because once pyridine is added above the surface of the zinc-porphyrin skeleton, the "edge-over-edge"dimer created from stacked formed rings has a high electrical conductance, minimal exciton thermal conductance, and a large thermal diffusivity on the order of 300 V K1. At room temperature, these variables add up to a projected ZT 4 figure of merit, the greatest ZT for a single organic molecule ever seen. The stacked arrangement of the porphyrin rings causes low phonon thermal conductance, which delays phonon transport across the edge-over-edge molecule and increases the Seebeck coefficient, resulting in a higher ZT value.